Analisis Perbandingan Tax Amnesty Jilid I dan Jilid II (Program Pengungkapan Sukarela) Serta Peluang Keberhasilannya - Uswatun Hasanah; Khairun Na'im; Elyani; Khamo Waruwu (Owner : Riset dan Jurnal Akuntansi, 2021)
The government has implemented the tax amnesty volume I in July 2016 and ended in March 2017. In early 2022, the government will plan to implement the tax amnesty volume II, which was introduced as the Voluntary Disclosure Program (PPS). This program refers to the Tax Harmonization Law Number 7 of 2021. Although the results obtained during the tax amnesty volume, I did not meet the target, in 2022 the government still plans to implement the tax amnesty volume II. For this reason, it is necessary to analyze the difference between the tax amnesty volume I and the tax amnesty volume II (PPS), as well as predict its effectiveness if this tax amnesty will be implemented later. This study method focuses on a comparative qualitative descriptive method in which data collection is carried out by taking from the library, website, law and articles discussing this tax amnesty. The results obtained are that there are fundamental differences between tax amnesty I and tax amnesty II. The differences are found in the data, rates, and tax subjects. For taxpayers who have participated in the 2016 tax amnesty volume I, the tariff charged is cheaper than those who do not participate in the first volume I tax amnesty and there are restrictions on subjects who may participate in the second tax amnesty. The effectiveness of this second volume of tax amnesty is predicted to be successful with a record that socialization must be maximal, there is no perception that the tax amnesty endangers honest taxpayers, and the view of taxpayers that this tax amnesty is the last tax amnesty so that there is a fear of not paying taxes and being subject to fines.